2000
DOI: 10.1002/1531-8249(200010)48:4<624::aid-ana9>3.3.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Axonal Guillain‐Barré syndrome: Relation to anti‐ganglioside antibodies and Campylobacter jejuni infection in Japan

Abstract: To clarify the relations of the axonal form of Guillain-Barré syndrome (GBS) to anti-ganglioside antibodies and Campylobacter jejuni infection, 86 consecutive Japanese GBS patients were studied. Electrodiagnostic criteria showed acute inflammatory demyelinating polyneuropathy in 36% of the patients and acute motor axonal neuropathy (AMAN) in 38%. Frequent anti-ganglioside antibodies were of the IgG class and against GM1 (40%), GD1a (30%), GalNAc-GD1a (17%), and GD1b (21%). Identified infections were C. jejuni … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
152
0
5

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 118 publications
(170 citation statements)
references
References 30 publications
13
152
0
5
Order By: Relevance
“…Ganglioside antibodies such as GM1 or GD1a are established as the cause of acute motor axonal neuropathy 61, 62. Little is known about the cellular pathophysiology in GM1 or GD1a‐positive patients, but in some cases, antibodies against specific epitopes are associated with specific clinical features 63.…”
Section: Discussionmentioning
confidence: 99%
“…Ganglioside antibodies such as GM1 or GD1a are established as the cause of acute motor axonal neuropathy 61, 62. Little is known about the cellular pathophysiology in GM1 or GD1a‐positive patients, but in some cases, antibodies against specific epitopes are associated with specific clinical features 63.…”
Section: Discussionmentioning
confidence: 99%
“…There have only been a few reports demonstrating the frequency of serum anti-ganglioside antibodies in GBSpatients who had been tested by ELISAfor more than 5 species of gangliosides, including at least anti-GMl, GDlb, GQlb, GDla and GM2 (12,17,30). In the largest study, Miyazaki et al showed that 241 (54.2%) of 445 GBSpatients had at 1:25,600 à"à" j j à" I 1:12,800 -à"à"à"à"à" : à" : à" j 1:6,400 -i à"à"à"à" : à"à"à"à"à" : à"à" 1:3,200 à"à" j à" j à" j 1:1,600-I à"à"à" j à"à"à" j à"à" 1:800 -à"à" !…”
Section: Discussionmentioning
confidence: 99%
“…As a result of this prevalence, it is known that some types of anti-ganglioside antibodies are specifically linked with the antecedent events or clinical features in GBS. Serum IgG anti-GMl antibodies with or without anti-GDIb antibodies, which are often present after Campylobacter jejuni enteritis (3,(13)(14)(15), sometimes cause acute motor axonal (AMAN) or motor and sensory axonal neuropathy (AMSAN) (16,17). IgM anti-GM2 antibodies occur in patients, frequently associated with facial palsy and sensory neuropathy, with an antecedent CMVinfection (9,18,19).…”
Section: Introductionmentioning
confidence: 99%
“…Immunophenotypic studies revealed a predominance of CD8 + T cells in GBS, in contrast to macrophage-rich infiltrates in paralytic rabies, correlating with high CSF IFN-γ and IL-6, and low tumor necrosis factor (TNF)-α and IL-4 [85]. The striking similarity in clinical, as well as pathological, changes between the paralytic form of rabies and GBS raised the possibility that the same immunopathogenetic mechanism implicated in GBS associated with Campylobacter jejuni, Mycoplasma pneumonia, cytomegalovirus, and Epstein-Barr virus could also be operative in paralytic rabies, with the development of autoantibodies to peripheral myelin due to molecular mimicry [86]. In fact, one of the initial historical cases of the acute motor sensory variant of GBS was found, on review, to be a case of paralytic rabies [87].…”
Section: Bat Rabiesmentioning
confidence: 99%
“…Subcutaneous routes have low seroconversion rates and a faster fall in antibody response [175]. The intradermal use of rabies vaccines is considered by the WHO as an acceptable alternative regimen as it requires less vaccine to produce a comparable degree of rabies protection [82,86]. Intradermal administration has become standard practice in a number of countries worldwide.…”
Section: Post-exposure Prophylaxismentioning
confidence: 99%